Central nervous system neuropeptide Y regulates mediators of hepatic phospholipid remodeling and very low-density lipoprotein triglyceride secretion via sympathetic innervation - Jennifer M. Rojas; Eveline Bruinstroop; Richard L. Printz; Aldijana Alijagic-Boers; Ewout Foppen; Maxine K. Turney; Leena George; Annette G. Beck-Sickinger; Andries Kalsbeek; Kevin D. Niswender (Elsevier, 2015)
Objective: Elevated very low-density lipoprotein (VLDL)-triglyceride (TG) secretion from the liver contributes to an atherogenic dyslipidemia that is associated with obesity, diabetes and the metabolic syndrome. Numerous models of obesity and diabetes are characterized by increased central nervous system (CNS) neuropeptide Y (NPY); in fact, a single intracerebroventricular (icv) administration of NPY in lean fasted rats elevates hepatic VLDL-TG secretion and does so, in large part, via signaling through the CNS NPY Y1 receptor. Thus, our overarching hypothesis is that elevated CNS NPY action contributes to dyslipidemia by activating central circuits that modulate liver lipid metabolism. Methods: Chow-fed Zucker fatty (ZF) rats were pair-fed by matching their caloric intake to that of lean controls and effects on body weight, plasma TG, and liver content of TG and phospholipid (PL) were compared to ad-libitum (ad-lib) fed ZF rats. Additionally, lean 4-h fasted rats with intact or disrupted hepatic sympathetic innervation were treated with icv NPY or NPY Y1 receptor agonist to identify novel hepatic mechanisms by which NPY promotes VLDL particle maturation and secretion. Results: Manipulation of plasma TG levels in obese ZF rats, through pair-feeding had no effect on liver TG content; however, hepatic PL content was substantially reduced and was tightly correlated with plasma TG levels. Treatment with icv NPY or a selective NPY Y1 receptor agonist in lean fasted rats robustly activated key hepatic regulatory proteins, stearoyl-CoA desaturase-1 (SCD-1), ADP-ribosylation factor-1 (ARF-1), and lipin-1, known to be involved in remodeling liver PL into TG for VLDL maturation and secretion. Lastly, we show that the effects of CNS NPY on key liporegulatory proteins are attenuated by hepatic sympathetic denervation. Conclusions: These data support a model in which CNS NPY modulates mediators of hepatic PL remodeling and VLDL maturation to stimulate VLDL-TG secretion that is dependent on the Y1 receptor and sympathetic signaling to the liver.